2021
DOI: 10.3390/diagnostics11081344
|View full text |Cite
|
Sign up to set email alerts
|

Surgically Induced Contrast Enhancements on Intraoperative and Early Postoperative MRI Following High-Grade Glioma Surgery: A Systematic Review

Abstract: For the radiological assessment of resection of high-grade gliomas, a 72-h diagnostic window is recommended to limit surgically induced contrast enhancements. However, such enhancements may occur earlier than 72 h post-surgery. This systematic review aimed to assess the evidence on the timing of the postsurgical MRI. PubMed, Embase, Web of Science and Cochrane were searched following Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Only original research articles describi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…A recent systematic review found that CE changes may be best evaluated between 24 and 48 h after surgery, confirming the Updated Response Assessment Criteria for High-Grade Gliomas [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…A recent systematic review found that CE changes may be best evaluated between 24 and 48 h after surgery, confirming the Updated Response Assessment Criteria for High-Grade Gliomas [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 68%
“…Only in recent years has attention been paid to Dynamic Susceptibility Contrast (DSC) sequences [ 19 , 20 , 21 , 22 ]. In pre-operative identification, the sensitivity and specificity of DSC appear to be high, at 94.7% and 93.7%, respectively, by the calculation of Cerebral Blood Volume (CBV) [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Rykkje and colleagues discussed the best timing for performing post-surgical MRI to evaluate the extent and effectiveness of surgical resection [ 46 ]. Increases in contrasts unrelated to the neoplastic tissues were observed at all times following surgery and even during surgery (intraoperative MRI).…”
Section: Advances In Diagnosismentioning
confidence: 99%
“…Several studies have reported thin linear new enhancements around the surgical margin seen during or immediately after surgery on T 1 -weighted images. 129 131 These anomalous enhancements are caused by disruption of the blood‒brain barrier or bleeding caused by surgical intervention or contrast leaking into the tumor cavity, and should not be confused with residual tumor. 132 The preoperative enhanced lesion and the intraoperatively and immediately postoperative occurring enhanced region must be carefully compared.…”
Section: Key Issues For Interpretation Of Iomr Imagesmentioning
confidence: 99%